Morphometric Measurements of Cranio-Vertebral Junction among Nepalese Population - Ranabhat, Kajan; Bishokarma, Suresh; Agrawal, Prity; Ghimire, Ram Kumar (Nepal Journal of Neuroscience, 2019)
The craniovertebral junction area refers to the osseous structures consisting of the occipital bone that surrounds the foramen magnum, the atlas, and the axis vertebrae. There is sparse literature about the morph metric measurement of craniovertebral junction region. We aim to derive a range of various measurements incraniovertebral junction area. This is a hospital based single center retrospective study conducted in our center among 100 consecutive computed tomography scans of craniovertebral junction obtained in adult patients who were admitted to our tertiary hospital for treatment of non-craniovertebraljunction conditions between 2017 and 2018.Various craniovertebral junction morphology parameters were measured and confidence interval at 95% were obtained the range at 2standard deviation. Among 100 patients studied, 51% of them were males while 49% were females. Mean age was 35.1±10.4 years with range from 15 to50 years. Computed tomography measurement of craniovertebral junction revealed meanders height of 30.8±2.5 mms, dento-clivaldistance was 5.9±1.6 mms and mean McRae’s distance of 34.2±2.49 mms. Similarly, anterioratlantodental interval was calculated to be1.83±0.47 mms and posterior atlantodentalinterval was 17.72±0.21 mms while Modified RW distance was 24.43±2.09 mms and Redlund Johnell distance was calculated to be 31.5±4.29mms. Normal morphometric measurements ofcraniovertebral junction can be useful for evaluating abnormalities of the craniovertebraljunction which can potentially improve the diagnostic criteria of most abnormalities.